Biosolids applied to land : advancing standards and practices (National Academies Press, 2002)
" ... this report ... searched for evidence on human health effects related to biosolids exposure and the technical methods and approaches used by EPA to establish its human-health-based chemical and pathogen standards for biosolids."--Page xi.